Perancangan Desain UI/UX Aplikasi Mobile Diet Anti-Inflamasi Bagi Penderita Lupus Dengan Metode Design Thinking - Agustina Widya Astuti; Aridhanyati Arifin (Fakultas Teknik Universitas Hamzanwadi, 2026)
Lupus or Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that attacks various organs in the body and impacts the quality of life of sufferers. ODAPUS needs to live a healthy lifestyle by maintaining a healthy diet, one of which is by implementing an anti-inflammatory diet that aims to reduce inflammation and prevent the recurrence of symptoms. However, limitations in digital media and access to accurate nutritional information make it difficult for ODAPUS to consistently follow a diet. This study aims to design a UI/UX for an anti-inflammatory diet mobile application using the Design Thinking method, which includes the stages of Empathize, Define, Ideate, Prototype, and Testing. In the Empathize stage, data was collected using a survey of 15 members of the Sahabat Cempluk Yogyakarta Community. This study produced a High-Fidelity Prototype with four main features, namely ODAPUS profile, calorie calculator, diet menu recommendations, and food preparation guidelines. The Testing stage used the online Focus Group Discussion (FGD) method, which was attended by 16 participants. The evaluation covered visual aspects, navigation, diet menu recommendation features, clarity of information, processing guides, colors and text, and suitability of needs. The evaluation results showed a 100% acceptance rate in all test aspects. Thus, the Design Thinking method proved to be effective in producing a simple, empathetic, and ODAPUS-friendly mobile application UI/UX design.